2011
DOI: 10.1371/journal.pone.0016905
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Electrical Currents to Probe EEG Brain Rhythms and Memory Consolidation during Sleep in Humans

Abstract: Previously the application of a weak electric anodal current oscillating with a frequency of the sleep slow oscillation (∼0.75 Hz) during non-rapid eye movement sleep (NonREM) sleep boosted endogenous slow oscillation activity and enhanced sleep-associated memory consolidation. The slow oscillations occurring during NonREM sleep and theta oscillations present during REM sleep have been considered of critical relevance for memory formation. Here transcranial direct current stimulation (tDCS) oscillating at 5 Hz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
173
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(181 citation statements)
references
References 62 publications
(83 reference statements)
6
173
1
1
Order By: Relevance
“…In healthy individuals, increasing spindles with zolpidem 66,67 , increasing sigma activity with transcranial stimulation 68,69 and enhancing the synchronization of sigma activity with slow oscillations using auditory closed-loop stimulation 70 all improve memory, while transcranial stimulation that decreases sigma activity impairs memory 71 . Only a few studies have attempted to improve cognition in schizophrenia by manipulating sleep oscillations.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy individuals, increasing spindles with zolpidem 66,67 , increasing sigma activity with transcranial stimulation 68,69 and enhancing the synchronization of sigma activity with slow oscillations using auditory closed-loop stimulation 70 all improve memory, while transcranial stimulation that decreases sigma activity impairs memory 71 . Only a few studies have attempted to improve cognition in schizophrenia by manipulating sleep oscillations.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reasons to explain this variability. Studies on fMRI 4 and electroencephalography (EEG) 5,6 reveal that although tDCS has the most activating effect on the underlying cortex, the stimulation evokes widespread changes in other regions of the brain. In addition, it has been shown that tDCS effects depend on the state of baseline cortical activity 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, it significantly decreased slow spindle activity (8-12 Hz) only frontally. These EEG changes were associated with a strong impairment of only declarative memory consolidation at recall after sleep (Marshall et al, 2011). Collectively, these findings strongly indicate that SO, SWA and frontal slow spindle activity reflect specific EEG mechanisms of hippocampus-dependent memory consolidation, which do not act beyond non-REM sleep/SWS.…”
Section: Overview Of Human Eeg Datamentioning
confidence: 69%
“…The stimulation did enhanced gamma (25-45 Hz) EEG activity during REM sleep, but it did not improve either declarative or procedural memory consolidation at morning recalls. Instead, this increase in gamma EEG during REM sleep resulted in a worsened mood, as assessed by positive and negative affect scale, in the morning after sleep, accompanied by worsening on working memory, as assessed by a word fluency test (Marshall et al, 2011). Collectively, these studies demonstrate that specific REM sleep EEG rhythms are involved in affective behavior.…”
Section: Overview Of Human Eeg Datamentioning
confidence: 80%